2012
DOI: 10.1063/1.4772780
|View full text |Cite
|
Sign up to set email alerts
|

Sub-microsecond pulsed atmospheric glow discharges with and without dielectric barrier

Abstract: The discharge characteristics and mechanism of glow discharges in atmospheric pressure helium excited by repetitive voltage pulses with and without dielectric barriers are numerically studied using a one-dimensional self-consistent fluid model. The waveforms of discharge current density show that one discharge event occurs during the voltage pulse with bare electrodes and two distinct discharge events happen at the rising and falling phases of voltage pulse with dielectric barrier electrodes, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…In figure 1(b), the duration of the voltage rise phase, plateau phase and falling phase are the same as in figure 1(a), but the voltage amplitude is increased to 2560 V due to the voltage drop across the dielectric plates [34], and the thickness of the dielectric plates is set to 1.5 mm with a relative permittivity of 7.5. It is obvious from figure 1(b) that there are double peak currents with amplitudes of 187.8 and 165.4 mA cm −2 at the rising and falling phases of applied pulsed voltage, respectively, which is consistent with the findings in [34,43,54,59]. However, in the barrier-free NPD, only a single current pulse appears at the end of the plateau phase of the applied voltage in figure 1(a), as also reported in the experimental observations in [25,34,42,44,45], which indicates that the new physical mechanism occurs as the dielectric is removed and the underlying physics should be further clarified by the computational data.…”
Section: Discharge Characteristics Of Barrier-free Npdssupporting
confidence: 87%
See 1 more Smart Citation
“…In figure 1(b), the duration of the voltage rise phase, plateau phase and falling phase are the same as in figure 1(a), but the voltage amplitude is increased to 2560 V due to the voltage drop across the dielectric plates [34], and the thickness of the dielectric plates is set to 1.5 mm with a relative permittivity of 7.5. It is obvious from figure 1(b) that there are double peak currents with amplitudes of 187.8 and 165.4 mA cm −2 at the rising and falling phases of applied pulsed voltage, respectively, which is consistent with the findings in [34,43,54,59]. However, in the barrier-free NPD, only a single current pulse appears at the end of the plateau phase of the applied voltage in figure 1(a), as also reported in the experimental observations in [25,34,42,44,45], which indicates that the new physical mechanism occurs as the dielectric is removed and the underlying physics should be further clarified by the computational data.…”
Section: Discharge Characteristics Of Barrier-free Npdssupporting
confidence: 87%
“…Furthermore, it has been proved that modulation of the pulsed voltage waveform, such as pulse rise rate and plateau voltage, could effectively optimize the corresponding discharge characteristics of NPDs for practical applications [25,26,[32][33][34][35][36]. Generally speaking, high-pressure NPDs are commonly achieved by means of a dielectric barrier covering the electrodes in the experiments [37][38][39][40][41]; however, considering that the dielectric layers may be contaminated after persistent usage, which would cause them to lose their ability to stabilize NPDs, it is desirable to dispense with the use of a dielectric barrier in the various applications [34,42,43]. Walshʼs group reported that a barrier-free sub-microsecond pulsed discharge was achieved within the kilohertz range in experiments [44], and Iza et al introduced a hybrid computational model to explore the electrical properties of the barrier-free multi-pulse discharge at atmospheric pressure [25].…”
Section: Introductionmentioning
confidence: 99%
“…This is also because of the elevated proportion of the sheath thickness to discharge gap distance as the thickness of the plasma bulk region is reduced by the reduction in the discharge gap distance, where the electron density is high and the electron energy is low. [27] Conversely, when the discharge gap is reduced from 1.00 mm to 0.12 mm, the population of energetic electrons increases from 0.34 × 10 10 m −1 to 1.08 × 10 11 m −1 owing to the elevated proportion of energetic electrons and discharge intensity, as shown in Fig. 5.…”
Section: Discharge Characteristics and Dynamics At The Instants Of Di...mentioning
confidence: 94%
“…两个电极之间施加正弦电压 , 其中, V 0 为幅值, f为频率. 放电背 景气体为纯氦气, 反应集合来自文献[35]. 使用有 限差分法数值求解上述方程(1)-(4), 其中方程(2) 结合改进的Scharfetter-Gummel (SG)算法.…”
unclassified